Poems - Vargas Bolaños, Juan Carlos (2005)
Botticelli's "Primavera". Leonardo's "Last Supper". Paolo Uccello's "Christ Crucified, with Saint John the Baptist, the Virgin, Saint John The Evangelist, and Saint Francis". Botticelli's "The Birth of Venus". Botticelli's "Costello Annunciation". Mantenga's "Dead Christ". Raphael's "Sistine Madonna". Masaccio's "Trinity".